KUALITAS PAPAN KOMPOSIT KULIT BATANG SAGU (Metroxylon sp) DAN LIMBAH PLASTIK POLIPROPILENA BERDASARKAN PENAMBAHAN COMPATIBILIZER - Sumimi, .; Farahdiba, .; Nurhaida, .; Setyawati, Dina (JURNAL HUTAN LESTARI, 2016)
Wood is a basic requirement in the industrial activity such as constructions and furniture. While timber production decreased so that required an efficient utilization of wood. The solution to overcome this problem is use of sago bark in the form of composite board. Plastic is a material consisting of artificial inorganic chemicals are quite harmful to the environment so it is necessary to increase the value of plastic. In the process of making composite board using compatibilizer to improve the bonding between the fibers. The study aims to determine the quality of the composite board made from sago bark and polypropylene plastic waste based on addition of compatibilizer. Percentage of compatibilizer used 0%, 2,5%, and 5% of the weight of the plastic. Composite board size was 30 cm x 30 cm x 1 cm with a target density of 0.7g/cm3 at compression 25 kg/cm2 with temperature 180ÂºC for 10 minutes. Evaluation the physical properties (density, moisture content,thickness swelling and water absorption ) and mechanical properties (modulus of elasticity, modulus of rupture, internal bonding and strong hold the screws) was conducted according to standard JIS A 5908-2003. The result of research showed that the highest quality of composite board was achieved on the highest addition with percentage compatibilizer 5%. Keywords: BPO, compatibilizer, composite board, MAH, plastics polipropilena, sago bark.